Where Do People in Nigeria Get Their Contraception? - Ladipo, Oladapo A (Public Library of Science, 2005)
Knowing where users obtain different contraceptive methods is useful for planning service delivery, argues Ladipo, who examines a new study on contraception in Nigeria.